Age‐related association between white matter integrity and cerebral blood flow in white matter. Issue 4 (1st February 2022) - Jekel, Ciara; Kim, Donghoon; Hughes, Tim M.; Lockhart, Samuel N.; Whitlow, Christopher T.; Craft, Suzanne; Baker, Laura D.; Okonmah‐Obazee, Stephanie; Bobinski, Matthew; Jung, Youngkyoo
Abstract: Background: Alzheimer's disease (AD) has a long preclinical phase that is often preceded by reduced white matter (WM) integrity; further, impaired cerebrovascular function is associated with AD biomarkers. However, the intersection of WM structure and cerebrovascular function in the risk and progression of Alzheimer's disease is unclear. We examined the relationship between WM structure and cerebrovascular function in younger and older adults at risk for AD. Method: Participants enrolled in the Wake Forest Alzheimer's Disease Research Center Clinical Core underwent: 3T MRI scan including neurite orientation dispersion and density imaging (NODDI) and arterial spin labeling (ASL), clinical exams, cognitive testing, and adjudication. Intra‐cellular volume fraction (ICVF) and cerebral blood flow (CBF) were obtained from NODDI and ASL, respectively. Multivariable linear regression analyses were performed to investigate the relationship between ICVF and CBF in 48 WM regions (JHU ICBM‐DTI‐81 atlas). Analyses were performed separately on participants grouped by age (median split at ≥71 years) and adjusted for covariates: sex, race, and cognition status, and grouped by cognitive status and adjusted for covariates: sex, race, and age. The Benjamini & Hochberg false discovery rate method was used to test multiple hypothesis across ROIs. Result: 330 participants completed MRI sequences for WM structure and perfusion (mean age: 70.3±8 yrs.; M/F: 105/225; 283 White, 47 Black or African American; 198 cognitively normal, 132 mild cognitive impairment (MCI)). The older group had lower mean ICVF and mean WM CBF (0.70±0.05; 18.9±3) than the younger group (0.73±0.04; 19.7±3). In the older group, mean ICVF was positively related to mean WM CBF (p<0.01). In older participants (≥71) there were eight regions where ICVF and CBF were positively related (corrected p<0.05). In younger participants (<71) there was one region where ICVF and CBF were positively related (fornix column and body; corrected p<0.05). When grouped by cognitive status (normal/MCI), no association was found between mean ICVF and mean WM CBF. Conclusion: Generally, reduced integrity in WM structure is associated with reduced CBF. This association appears related to age, not cognitive status. Differences in the associated regions by age suggest potential effects of brain aging on WM structure and CBF.